Positioning community pharmacies in terms of access and information and communication technologies use in modern cities of Malaysia. Issue 3 (9th July 2018) - KC, Bhuvan; Mohamed Izham, Mohamed Ibrahim
Abstract: Modern cities are the hub of Malaysian economic growth and urbanisation. These cities are sprawling across Malaysia and are built as an urban eco-system with an integrated physical, social, economic and public infrastructure enabled through the information and communication technologies (ICT) applications. Due to their integrated design and land scarcity, these cities are built around multi-storey housing condominiums and high-rise residential buildings with shopping and other facilities instead of the colonies with stand-alone houses of old cities. Hence, the community pharmacies located in the market town of old cities now have to reposition themselves to adapt to the need and design of these modern cities. This article will briefly discuss the positioning of community pharmacies in modern cities of Malaysia in terms of geographical and physical accessibility, embracing the ICT application and business positioning.